2002
DOI: 10.1007/s00441-001-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical coding of neurons expressing δ- and κ-opioid receptor and type I vanilloid receptor immunoreactivities in the porcine ileum

Abstract: Opioid drugs have profound antidiarrheal and constipating actions in the intestinal tract and are effective in mitigating abdominal pain. Mediators of intestinal inflammation and allergy produce increased mucosal secretion, altered bowel motility and pain due to their ability to evoke enteric secretomotor reflexes through primary afferent neurons. In this study, the distribution of delta- and kappa-opioid receptor (DOR and KOR, respectively) immunoreactivities in chemically identified neurons of the porcine il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 35 publications
6
51
3
1
Order By: Relevance
“…However, the expression of TRPV1 in intrinsic enteric neurons is still controversial. Myenteric neurons were found to be TRPV1 immunoreactive in the guinea pig colon and ileum (Anavi-Goffer et al 2002;Anavi-Goffer and Coutts 2003), in the rat GI tract (Akiba et al 2001;Anavi-Goffer et al 2002;Anavi-Goffer and Coutts 2003), and in the porcine ileum (Kulkarni-Narla and Brown 2001; Poonyachoti et al 2002). Chan et al (2003) reported TRPV1 expression in submucosal and myenteric neurons in the human rectum.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of TRPV1 in intrinsic enteric neurons is still controversial. Myenteric neurons were found to be TRPV1 immunoreactive in the guinea pig colon and ileum (Anavi-Goffer et al 2002;Anavi-Goffer and Coutts 2003), in the rat GI tract (Akiba et al 2001;Anavi-Goffer et al 2002;Anavi-Goffer and Coutts 2003), and in the porcine ileum (Kulkarni-Narla and Brown 2001; Poonyachoti et al 2002). Chan et al (2003) reported TRPV1 expression in submucosal and myenteric neurons in the human rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Both substance P-and CGRP-containing neural cells have been demonstrated in the submucous plexus and a lamina propria subplexus of the intestine (10,25,31,49,50,53,56,59,62), but some controversy has been raised about the existence of neural cell bodies in the esophageal submucosa. Substance P-and CGRPcontaining neural cells, however, have been demonstrated in the human esophagus submucous plexus (55) and epithelium (54).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining smooth muscle layer was cut into 2-mm circular muscle strips, which were mounted in separate 1-ml muscle chambers and used for electrical field stimulation (EFS), as previously described in detail (6). The esophageal mucosal tube consisted of epithelial cells, lamina propria, muscularis mucosae, and submucosa, including submucosal and lamina propria neurons (10,25,31,49,50,53,56,59,62), with the epithelial layer on the inside. The separation between mucosal sac and circular muscle strips was as close to the inner layer of the circular muscle as could be surgically achieved under the dissecting microscope; thus the sac included the submucosa, and it seems reasonable that whatever came out of the sac into the supernatant would directly affect the muscle layer.…”
Section: Methodsmentioning
confidence: 99%
“…19 Preincubation of CGRP antiserum with its blocking peptides in 30-fold excess eliminated specific immunoreactivity. Omission of primary antibodies resulted in an absence of specific immunoreactivity.…”
Section: Immunohistochemistrymentioning
confidence: 99%